Muscle Transposition in Exposed Tibia - S. S. Gill; Raj Bahadur; O. N. Nagi (Indian Journal of Plastic Surgery)
Muscle Transposition along with immediate or delayed fresh split skin grafting has been contemplated in fifteen cases of open fractures of the leg bones where the tibia was exposed. The resuits of this procedure are satisfactory and are usually better in those cases where muscle transposition and skin grafting were done at the first stage. Minor complications like partial necrosis of the skin graft and muscle atrophy has been observed in few cases.